Swoistość konstrukcji rozwiązań prawnych postępowania administracyjnego a jedność funkcji prawa - Majchrzak, Bartosz (Kwartalnik Prawa Publicznego, 2017)
This article identifies the specific legal constructs of administrative procedure, distinguishing these proceedings from criminal and civil ones. Then, the specific functions of these constructs were determined to refer later to the general functions of administrative procedure, the function of administrative substantive law as well as the function of the legal system as a whole.